Avaliação das atividades antiinflamatória e antinociceptiva do acetato de lupeol isolado de Himatanthus drasticus (MART.) Plumel : Apocynaceae (Janaguba) - Lucetti, Daniel Luna (2010)
The lupeol acetate (FAL), isolated from the latex extracted of the stem of Himatanthus drasticus (APOCYNCEAE) is chemically classified as a pentacyclic triterpene belonging to the lupane class, was evaluated in nociception and inflammation models. In the writhing test induced by acetic acid (10 ml/kg, i.p.) in mice, FAL (50 and 100 mg/kg, i.p.) significantly reduced the number of writhing in 56 and 61%, respectively, and indomethacin (10 mg/kg, i.p.) reduced by 66%. In the formalin test, FAL (25 and 50 mg/kg, i.p.) significantly reduced the time spent by the animal licking the paw, both in the initial phase (21 and 46.5%, respectively) and in the late phase (57 , 6, and 61.3%, respectively) and morphine (7.5 mg/kg, i.p.) reduced by 62 and 91%, respectively. Pretreatment with naloxone (2 mg/kg, i.p.) significantly reversed the effects of FAL and morphine in both the early and in late phase in formalin test. In the carrageenan induced paw oedema, FAL (10, 25 and 50 mg/kg, i.p.) reduced in significant way the oedema volume in the 1st, 2nd and 3rd hour after carrageenan application (1%, 50μl, s.p.). Histopathologic analysis of mice paw tissue subjected to carrageenan, showed significant reductions in oedema and cellular infiltration. In the immunohistochemical staining in mice paw tissue subjected to carrageenan stimulus, the FAL (50mg/kg, i.p.) induced a slight reduction in the expression of TNF-α, but caused a significant reduction of tissue iNOS levels. In the dextran induced paw oedema, FAL (12.5 and 25 mg/kg, i.p.) significantly reduced the oedema volume in the 2nd and 3rd hour after dextran application (12%, 50μl, s.p.). In carrageenan-induced peritonitis, FAL (1, 10 and 20 mg/kg, i.p.) significantly reduced the number of leukocytes at 56, 80 and 92%, respectively. Pentoxifylline (1 and 25mg/kg, i.p.) inhibited by 39 and 68%, respectively, the number of leukocytes. In the myeloperoxidase (MPO) enzyme inhibition test, FAL (10, 25, 50 and 100 μg/ml) reduced the activity of MPO at 36, 80, 79 and 74%, respectively. The FAL showed no antioxidant activity in DPPH test. Together, these data reveal that the FAL has antinociceptive activity, which can be explained by its ability in mimicking the endogenous opioids effects, and antiinflammatory, explained by TNF-α and iNOS expression decreased, as well as by the myeloperoxidase activity decreasing, resulting in inhibition of leukocyte migration to the focus of inflammation.